2002
DOI: 10.4315/0362-028x-65.7.1142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of UV Irradiation on Selected Pathogens in Peptone Water and on Stainless Steel and Chicken Meat

Abstract: Effects of intensity and processing time of 254 nm UV irradiation on Listeria monocytogenes, Escherichia coli O157:H7, and Salmonella Typhimurium were investigated. Intensities measured at 5.08, 10.1, 15.2, and 20.3 cm from the light source were 1.000, 500, 250, and 150 microW/cm2, respectively. Intensities of 250 or 500 microW/cm2 reduced all suspended pathogen cells in peptone water about 5 log cycles after 2 min and completely inactivated L. monocytogenes and E. coli O157:H7 after 3 min by reductions of 8.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 12 publications
2
41
0
1
Order By: Relevance
“…Greater inactivation rate at 100 μW cm − 2 as indicated by lower D UV -value was reported for TSA (15 s), followed by pork skin (595 s) and pork muscle (1163 s). Similar results were also reported for beef steak (Stermer, Lasater-Smith, & Brasington, 1987), chicken halves (Wallner-Pendleton, Sumner, Froning, & Stetson, 1994), poultry skin (Sumner, Wallner-Pendleton, Froning, & Stetson, 1995), and chicken meat (Kim, Silva, & Chen, 2002). In their study (UV: 250-500 μW cm − 2 ; 3 min) on chicken meat, peptone water and stainless steel, Kim et al (2002) reported 5-log reduction of Salmonella Typhimurium in peptone water and stainless steel compared to only 1-log and 0.36-log reductions in chicken meat with and without skin respectively.…”
Section: Ultraviolet Irradiationsupporting
confidence: 90%
“…Greater inactivation rate at 100 μW cm − 2 as indicated by lower D UV -value was reported for TSA (15 s), followed by pork skin (595 s) and pork muscle (1163 s). Similar results were also reported for beef steak (Stermer, Lasater-Smith, & Brasington, 1987), chicken halves (Wallner-Pendleton, Sumner, Froning, & Stetson, 1994), poultry skin (Sumner, Wallner-Pendleton, Froning, & Stetson, 1995), and chicken meat (Kim, Silva, & Chen, 2002). In their study (UV: 250-500 μW cm − 2 ; 3 min) on chicken meat, peptone water and stainless steel, Kim et al (2002) reported 5-log reduction of Salmonella Typhimurium in peptone water and stainless steel compared to only 1-log and 0.36-log reductions in chicken meat with and without skin respectively.…”
Section: Ultraviolet Irradiationsupporting
confidence: 90%
“…Kim et al (22) also observed that Salmonella Typhimurium was more resistant than E. coli O157:H7, but Yaun et al (50) reported that UV resistance of Salmonella and E. coli O157:H7 did not differ, and Gabriel et al (14) demonstrated that Salmonella Typhimu- . The log 10 cycles of injured cells were calculated by subtracting the log 10 number of survivors in the nonselective media (TSAYE) from the log 10 number of survivors in the selective media.…”
Section: Discussionmentioning
confidence: 99%
“…Lyon, Fletcher, and Berrang (2007) reported an approximate 2 log reduction in viable L. monocytogenes on UV-treated broiler breast fillets, and Kim, Silva, and Chen (2002) also reported that some selected pathogens on chicken meat were reduced by 0.36-1.28 log CFU/g after UV-C treatment at 5 W/m 2 for 3 min. These reports are in good comparison with our results.…”
Section: Effect Of Uv-c Irradiation On the Survival Of Pathogenic Bacmentioning
confidence: 95%